1993
DOI: 10.1056/nejm199310143291604
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Lymphedema of the Arms and Legs with 5,6-Benzo-[alpha]-pyrone

Abstract: 5,6-Benzo-[alpha]-pyrone results in slow but safe reduction of lymphedema of the extremities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(131 citation statements)
references
References 6 publications
3
122
0
6
Order By: Relevance
“…Only two used validated Palliative Medicine QoL instruments. 25,27 One of these two studies reported significant improvement of QoL in the treatment group, while the other was a pilot trial with insufficient power to detect any difference in QoL. All evaluated treatments appeared to be safe, although three studies did not state whether side effects were specifically assessed.…”
Section: Patient-reported Outcomes and Side Effects Of Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two used validated Palliative Medicine QoL instruments. 25,27 One of these two studies reported significant improvement of QoL in the treatment group, while the other was a pilot trial with insufficient power to detect any difference in QoL. All evaluated treatments appeared to be safe, although three studies did not state whether side effects were specifically assessed.…”
Section: Patient-reported Outcomes and Side Effects Of Treatmentsmentioning
confidence: 99%
“…Although our results provided limited evidence to support current clinical decision-making, the included studies [24][25][26][27][28][29][30] could guide the planning of future studies.…”
Section: Recommendations For Future Studies On the Management Of Lllmentioning
confidence: 99%
“…• Benzopyrones, such as coumarin, 6 are not available for routine use in the U.S. at this time. Although bioflavenoids 7 are readily available, long term studies have not yet documented the efficacy of this pharmacologic approach.…”
mentioning
confidence: 99%
“…Flavonoids help to prevent platelets sickness and hence platelets aggregation [57]. The presence of coumarin in P. amarus, E. heterophylla, P. nigrum, A. conyzoides and G. latifolium enable these plants to carry out various pharmacological activities such as edema modification, faster reabsorption of edematous fluids, treatment of lymphedema, etc [58].…”
Section: Phytochemical Screening Of Plants Extractsmentioning
confidence: 99%